Inkjet printable-photoactive all inorganic perovskite films with long effective photocarrier lifetimes. (13th April 2018) - Ilie, C C; Guzman, F; Swanson, B L; Evans, I R; Costa, P S; Teeter, J D; Shekhirev, M; Benker, N; Sikich, S; Enders, A; Dowben, P A; Sinitskii, A; et al.
Abstract: Photoactive perovskite quantum dot films, deposited via an inkjet printer, have been characterized by x-ray diffraction and x-ray photoelectron spectroscopy. The crystal structure and bonding environment are consistent with CsPbBr3 perovskite quantum dots. The current–voltage ( I – V ) and capacitance–voltage ( C – V ) transport measurements indicate that the photo-carrier drift lifetime can exceed 1 ms for some printed perovskite films. This far exceeds the dark drift carrier lifetime, which is below 50 ns. The printed films show a photocarrier density 10 9 greater than the dark carrier density, making these printed films ideal candidates for application in photodetectors. The successful printing of photoactive-perovskite quantum dot films of CsPbBr3, indicates that the rapid prototyping of various perovskite inks and multilayers is realizable.